數位教科書對學生全球公民素養的啟示－以PISA 2022為例 - 陳榮政(Jung-Cheng Chen); 姜繼旺(Chi-Wang Chiang) (Jiao ke shu yan jiu, 2024)
This paper examines the potential for students within the context of digitalized textbooks to establish closer connections with global society. It explores the implementation of digital textbooks across various countries and analyzes data from the Programme for International Student Assessment (PISA) 2022 database, which includes data on 257,569 students aged 15 years from 32 countries. These data are used to analyze the differences in information and communication technology (ICT) competence between students in countries that use digital textbooks and those that do not. The findings indicate the following. First, many countries emphasize the integration of digital technology into education, focusing on the development of digital textbooks and educational resources. Second, students in Taiwan typically exhibit a high level of ICT competence, substantially surpassing the international average in the dimensions of “accessing, evaluating, and managing information and data” and “problem-solving in a digital conte